2022
DOI: 10.3389/fimmu.2021.795626
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Enzyme Triosephosphate Isomerase 1 and Nicotinamide Phosphoribosyltransferase, Two Independent Inflammatory Indicators in Rheumatoid Arthritis: Evidences From Collagen-Induced Arthritis and Clinical Samples

Abstract: Metabolic intervention is a novel anti-rheumatic approach. The glycolytic regulator NAMPT has been identified as a therapeutic target of rheumatoid arthritis (RA), while other metabolic regulators coordinating NAMPT to perpetuate inflammation are yet to be investigated. We continuously monitored and validated expression changes of Nampt and inflammatory indicators in peripheral while blood cells from rats with collagen-induced arthritis (CIA). Gene transcriptional profiles of Nampt+ and Nampt++ samples from id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Previously, we reported that intensified inflammation in rheumatic subjects was accompanied by up-regulation of glycolytic enzymes, and triosephosphate isomerase 1 (TPI1) was identified as a new RA-related inflammatory indicator. 8 Meanwhile, it revealed that silent information regulator 1 (SIRT1) expression deficiency was another hallmark of RA-related inflammation based on data collected from collagen-induced arthritis (CIA), which conforms to the changes observed in RA patients. 8 Being an intersection of metabolism and immune regulatory signaling networks, SIRT1 promotes oxidative phosphorylation and M2 polarization of monocytes and macrophages.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Previously, we reported that intensified inflammation in rheumatic subjects was accompanied by up-regulation of glycolytic enzymes, and triosephosphate isomerase 1 (TPI1) was identified as a new RA-related inflammatory indicator. 8 Meanwhile, it revealed that silent information regulator 1 (SIRT1) expression deficiency was another hallmark of RA-related inflammation based on data collected from collagen-induced arthritis (CIA), which conforms to the changes observed in RA patients. 8 Being an intersection of metabolism and immune regulatory signaling networks, SIRT1 promotes oxidative phosphorylation and M2 polarization of monocytes and macrophages.…”
Section: Introductionmentioning
confidence: 69%
“… 8 Meanwhile, it revealed that silent information regulator 1 (SIRT1) expression deficiency was another hallmark of RA-related inflammation based on data collected from collagen-induced arthritis (CIA), which conforms to the changes observed in RA patients. 8 Being an intersection of metabolism and immune regulatory signaling networks, SIRT1 promotes oxidative phosphorylation and M2 polarization of monocytes and macrophages. 9 , 10 These orchestrated functions endow SIRT1 with notable anti-inflammatory capacity.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Accumulating evidence indicates that metabolic disorders can trigger systemic inflammation, which in turn may play a role in pathophysiology or even aggravate the disease itself ( Wang et al, 2015 ; Wenzl et al, 2021 ). Furthermore, recent studies also inspired that therapies targeting to restore metabolic homeostasis have the potential to treat inflammation damage ( Zhuo et al, 2012 ; Lei et al, 2021 ). Therefore, studies focusing on the metabolic regulation of gallic acid may be valuable to explore the therapeutic effect and potential mechanisms of the candidate in the cure of inflammation disorder.…”
Section: Introductionmentioning
confidence: 99%